Female-to-male to mistress: A layered account of layered performances. (February 2021) - Levine, Ethan Czuy
Professionals in bondage and discipline, dominance and submission, and sadism and masochism (BDSM) have received minimal attention in the literature on sex work. Moreover, investigations of performance in sex work have focused overwhelmingly on cisgender women professionals, and tended to emphasize laborer–client encounters within paid sessions while neglecting encounters among colleagues. In this article, I engage in sociological introspection to provide a layered autoethnographic account of dungeon labor. I draw upon 10 months' experience as a White, Jewish, queer, transmasculine person who enacted a White, sometimes Jewish, queer, cisgender womanhood throughout workplace encounters. Analyses emphasize gendered and sexual normativities, racism and discourses of client "taste, " violence in the workplace, and tensions between dungeon laborers' professional personas and sense of authenticity.